Effect of Ionic Liquid on Silver-Nanoparticle-Complexed Ganoderma applanatum and Its Topical Film Formulation - Pattwat Maneewattanapinyo; Wiwat Pichayakorn; Chaowalit Monton; Nattakan Dangmanee; Thaniya Wunnakup; Jirapornchai Suksaeree (MDPI AG, 2023)
Imidazolium-based ionic liquids have been widely utilized as versatile solvents for metal nanoparticle preparation. Silver nanoparticles and Ganoderma applanatum have displayed potent antimicrobial activities. This work aimed to study the effect of 1-butyl-3-methylimidazolium bromide-based ionic liquid on the silver-nanoparticle-complexed G. applanatum and its topical film. The ratio and conditions for preparation were optimized by the design of the experiments. The optimal ratio was silver nanoparticles: G. applanatum extract: ionic liquid at 97:1:2, and the conditions were 80 °C for 1 h. The prediction was corrected with a low percentage error. The optimized formula was loaded into a topical film made of polyvinyl alcohol and Eudragit®, and its properties were evaluated. The topical film was uniform, smooth, and compact and had other desired characteristics. The topical film was able to control the release of silver-nanoparticle-complexed G. applanatum from the matrix layer. Higuchi's model was used to fit the kinetic of the release. The skin permeability of the silver-nanoparticle-complexed G. applanatum was improved by about 1.7 times by the ionic liquid, which might increase solubility. The produced film is suitable for topical applications and may be utilized in the development of potential future therapeutic agents for the treatment of diseases.